Energy Efficiency of Personal Health Records - Coral Calero; José Luis Fernández-Alemán; Javier Mancebo; José A. García-Berná; Félix García; Ambrosio Toval (Proceedings, 2018)
Personal Health Records (PHR) are electronic tools managed by the patients themselves, allowing them to store and consult health data anywhere and at any time using an electronic device. Precisely because of the type of users they are aimed at, it is essential to guarantee that PHR are easy to use. However, having a PHR that is usable does not mean that it is the best in terms of energy efficiency. Taking into account the large number of users that this type of portal is aimed at, achieving savings in energy consumption when running the portal’s tasks can have a considerable impact. In this paper we present an initial approach that studies the interaction between usability and energy efficiency of PHRs, attempting to determine if a given PHR makes efficient use of the resources it needs for the execution of its tasks. To do this, we have used the EET device, which allows us to collect the consumption of different hardware components when running software (in our case the PHR), and the usability criteria defined by Dix.